An emerging market for corporate control? The Mannesmann takeover and German corporate governance - Martin Höpner; Gregory Jackson (Max-Planck-Institut für Gesellschaftsforschung, 2001)
Corporate governance in Germany is often described as a bank-oriented, block-holder or stakeholder model where markets for corporate control have not played a significant role. This case study of the hostile takeover of Mannesmann AG by Vodafone in 2000 demonstrates how systemic changes during the 1990s have eroded past institutional barriers to takeovers. These changes include the strategic reorientation of German banks from the house bank to investment banking, the growing consensus and productivity orientation of employee co-determination and corporate law reform. A significant segment of German corporations are now subjected to a market for corporate control. The implications for the German model are examined in light of both claims by agency theory for the efficiency of takeover markets, as well as the institutional complementarities within Germany's specific variety of capitalism. While the efficiency effects are questionable, the growing pressures for German corporations to achieve the higher stock market valuations of their Anglo-American competitors threaten the distributional compromises underlying the German model.
Keywords: 300; Übernahme; Corporate Governance; Shareholder Value; Deutschland